Systematical assessment of digit ratio in a female masculinization disease: polycystic ovary syndrome - Yan, Xueqi; Zhu, Aiqing; Li, Yexing; Yang, Ziyi; Wang, Yuteng; Liu, Li; Liu, Wei; Liu, Dan; Li, Fenghua; Du, Juan; Cheng, Fang; Gao, Xueying; et al. (Frontiers in Endocrinology, 2023)
Background In recent years, the right ratio of 2nd and 4th digit length (2D:4D) is regarded as an anatomical marker of prenatal testosterone exposure. Polycystic ovary syndrome (PCOS) is a female masculinized disease and is determined by prenatal testosterone exposure. Whether the ratio in the right hand of PCOS women is reduced or not compared with non-PCOS women is under debate. To further investigate the relationship between PCOS and digit ratio, we systematically measured all the digit ratios. Methods We recruited 34 non-PCOS women, 116 PCOS women, and 40 men and systematically measured all the ratios of digit length (2D:3D, 2D:4D, 2D:5D, 3D:4D, 3D:5D, and 4D:5D) of right hands and left hands. Results Left 2D:3D, 2D:4D, and 2D:5D in men were significantly lower than those in non-PCOS women. Significantly lower digit ratios of left 2D:3D and 2D:4D were observed in PCOS compared with non-PCOS women. In the subgroup analysis, the left ratio of digit length in 2D:3D and 2D:5D of the hyperandrogenism subgroup was lower than that of the non-hyperandrogenism subgroup without statistical significance. The logistic regression model of PCOS revealed that 2D:3D, 2D:4D, 2D:5D, and 3D:4D of left hands were statistically related to the diagnosis of PCOS among all the digit ratios. Conclusion Not only 2D:4D but also other digit ratios, such as 2D:3D and 2D:5D, are a marker of prenatal testosterone exposure and may be an anatomical marker of PCOS. The majority of these significant differences included left 2D, with the following order: non-PCOS women > PCOS women > men.